Study and comparison of major decomposition algorithms for polarimetric radar image processing - Goh, Jerome Siak Boon (Nanyang Technological University, 2022)
Synthetic-aperture radar (SAR) is method widely deployed to recreate accurate high-resolution reconstructions of the earth’s surface. Polarimetric synthetic aperture radar (PolSAR) in particular, is a method that recreates images of the terrain via measurement of the polarimetric properties of scatterers.